(untitled) (Revista Ciência Agronômica, 2020)
Due to the environmental impact generated using fungicides, new alternatives for disease control have been arising, such as the use of nutrients that may act on the development of certain pathogens or decrease the host susceptibility to diseases. The objective of this work was to verify if chelates of calcium, copper, manganese and zinc inhibit the germination of Puccinia sorghi, Cercospora sp. and Exserohilum turcicum spores. Two experiments were carried out: the first with agar-water culture medium, where the treatments and spores were placed at the same moment and the second using corn leaves as substrate, where treatments were administered zero, one, two, three, four and five hours after the spores are sprayed. Calcium, copper, manganese and zinc products were used as treatments in the form of chelate 15%, 5%, 15% and 10%, fungicide (strobilurine and triazole, 20% azoxistrobin and 8% ciproconazole + triazole, 25% propiconazole) and distilled water. The spores were counted 24 hours after the application of the treatments. In the first experiment, chelates showed an average reduction of 39% in both germination of P. sorghi and Cercospora sp. spores. For the second assay, the same pathogens had a mean reduction of 52%, 59%, 77%, 87%, 81% and 64% for P. sorghi and 40%, 33%, 17%, 18%, 4% and 2% for Cercospora sp., both at zero, 1, 2, 3, 4 and 5 hours after treatment, respectively. E. turcicum had no inhibitory effect under treatments. The metal-chelates tested were fungitoxic to P. sorghi and Cercospora sp. spores.